PEMBERDAYAAN MASYARAKAT MISKIN MELALUI KELOMPOK USAHA BERSAMA (STUDI PADA KELOMPOK USAHA BERSAMA DESA GRECOL KECAMATAN KALIMANAH, KABUPATEN PURBALINGGA - Dessy Permatasari Pratiwi; Retno Sunu Astuti (Journal of Public Policy and Management Review, 2019)
Poverty in Purbalingga Regency is still relatively high, so the government carried out community empowerment through the Joint Business Group (KUBE) in Grecol Village, Kalimanah District in the Skills and Ability Improvement Activities of Social Economic Prone Families. The method used is a qualitative method with data collection techniques of observation, interviews, and documentation. Determination of the subject using purposive sampling techniques, the validity of the data using data triangulation techniques. The results of the study show that the empowerment stage is through the preparation stage, the implementation stage, the business development stage and the termination stage. The empowerment process for KUBE Grecol Village which consists of 5 groups is still not optimal in various aspects. In the inhibiting factor KUBE Grecol Village based on institutional, social and economic factors. Institutionally, the number of members is reduced due to internal group factors, the division of tasks becomes an obstacle for each group because of the busyness of each member, for administering KUBE Grecol Village activities is still empty because they still do not understand the filling of activity administration books, for the commitment of KUBE members of Grecol Village is still lacking. From the social perspective on the quantity and quality of meeting members with the level of social participation of members is still a barrier because of the lack of cohesiveness of members of the KUBE Village Grecol. From an economic standpoint in the quantity and quality of KUBE management, Grecol village has different management, but basically due to the lack of ability to raise goats and the busyness of each member that makes responsibilities decrease by neglecting their duties as KUBE members. The advice that can be given needs to be improved coordination between DINSOSDALDUKKBP3A Purbalingga Regency and the Central Java Provincial Social Service in the guidance and supervision of KUBE members. For KUBE members, Grecol Village needs to be increased commitment and responsibility as KUBE members.